2002
DOI: 10.1046/j.1365-2893.2002.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Early viral clearance and sustained response in chronic hepatitis C: a controlled trial of interferon and ribavirin after high‐dose interferon induction

Abstract: High-dose induction with alpha-interferon induces early viral clearance of hepatitis C and combined with ribavirin enhances sustained response. We assess whether adding ribavirin after viral clearance obtained by alpha-interferon induction increased the rate of viral eradication.Forty-one naïve patients with chronic hepatitis C were randomised to receive, after 4 weeks of 10 mU daily of alpha-interferon (induction), 3 mU daily for 22 weeks and 3 mU thrice weekly for 26 weeks of either interferon alone (monothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11] Most of these studies investigated standard interferon and included both HCV genotype 1 and non-1 patients, with variable periods of induction (4-14 weeks). Induction with standard interferon has improved initial HCV RNA decay 11 and initial virological responses, 8 but has in general failed to improve SVR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6][7][8][9][10][11] Most of these studies investigated standard interferon and included both HCV genotype 1 and non-1 patients, with variable periods of induction (4-14 weeks). Induction with standard interferon has improved initial HCV RNA decay 11 and initial virological responses, 8 but has in general failed to improve SVR.…”
Section: Discussionmentioning
confidence: 99%
“…Induction with standard interferon has improved initial HCV RNA decay 11 and initial virological responses, 8 but has in general failed to improve SVR. [6][7][8][9][10][11] The exception is the study by Ferenci et al that demonstrated significantly higher SVR rates with high-dose daily interferon among the subgroup of patients with HCV genotype 1, although not in the overall study population. 4 Limited data exists on the efficacy of induction therapy with peginterferon alfa in patients infected with HCV genotype 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with genotype 1b and a high viral load, various studies including induction-dosing trials showed greater rates of early viral clearance. However, there were a few reports suggesting that early viral clearance was associated with a high prevalence of SVR [37,39,40] . Vrolijk et al [41] demonstrated that daily induction therapy might be benefi cial for IFN-resistant patients, but only when combined with adequate maintenance therapy of long duration.…”
Section: Discussionmentioning
confidence: 99%